Clinical Experience of Tian Yu in the Treatment of Hiccups by Using Xuan Zhe Chai Yue Recipe Combined with Diaphragmatic Three Needles - Zhao, Siyu; Dai, Lina; Li, Hui; Ma, Wensheng; Tian, Yu (Journal of Contemporary Medical Practice, 2025)
Upset, also known as “diaphragmatic spasm”, is a kind of qi against the upward impulse, the throat er er continuous sound, short and frequent sound and difficult to self-control for the characteristics of the disease. Chinese medicine will be categorized as “retch” category, that its pathology is mostly due to gastric qi upward reversal, diaphragm, and emotional disorders, dietary disorders, or cold and heat internal factors related. Modern medical treatment is often based on drug inhibition of phrenic nerve excitation, but it is easy to be accompanied by dry mouth, drowsiness and other side effects, and the efficacy of intractable retching is limited. Traditional Chinese medicine can significantly improve the symptoms and reduce the recurrence of the disease by combining acupuncture and medicine with evidence-based treatment, which has significant advantages. This article introduces the clinical experience of Dr. Tian Yu in the treatment of hiccups by combining xuan ge chai yue recipe with diaphragmatic three needles, which reflects the characteristics of holistic treatment in Chinese medicine.